2018
DOI: 10.1002/csr.1522
|View full text |Cite
|
Sign up to set email alerts
|

Employee engagement in CSR initiatives and customer‐directed counterproductive work behavior (CWB): The mediating roles of organizational civility norms and job calling

Abstract: This study aims to examine how service employees' perceptions of corporate social responsibility (CSR) affect their customer‐directed counterproductive work behavior (CWB) and the mediation of this link through their organizational civility norms and job calling. Working with a sample of 252 frontline employees in South Korea hotels, structural equation modeling is employed to test research hypotheses. The results of this study suggest that service employees' perceptions of CSR are negatively related to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 123 publications
2
53
0
Order By: Relevance
“…Micro-corporate social responsibility (CSR) studies are concerned with the impact of CSR on employees at the individual-level analysis via their sense-making of their organization's CSR acts (Rupp & Mallory, 2015). To date, although the micro-CSR literature has mainly demonstrated a positive link between employees' CSR perceptions and a variety of employee outcomes, such as affective commitment and identification, job satisfaction, work engagement, organizational citizenship behavior (OCB), customer-directed counterproductive work behavior, and creativity (Afsar, Cheema, & Javed, 2018;Aguinis & Glavas, 2012;De Roeck, Marique, Stinglhamber, & Swaen, 2014;Dhanesh, 2014;Glavas, 2016;Hur, Moon, & Lee, 2018;Zhou, Luo, & Tang, 2018), few studies have investigated how different kinds of CSR initiative affect employees' CSR perceptions (e.g., M. Farooq, Farooq, & Jasimuddin, 2014;O. Farooq, Payaud, Merunka, & Valette-Florence, 2014;O.…”
Section: Introductionmentioning
confidence: 99%
“…Micro-corporate social responsibility (CSR) studies are concerned with the impact of CSR on employees at the individual-level analysis via their sense-making of their organization's CSR acts (Rupp & Mallory, 2015). To date, although the micro-CSR literature has mainly demonstrated a positive link between employees' CSR perceptions and a variety of employee outcomes, such as affective commitment and identification, job satisfaction, work engagement, organizational citizenship behavior (OCB), customer-directed counterproductive work behavior, and creativity (Afsar, Cheema, & Javed, 2018;Aguinis & Glavas, 2012;De Roeck, Marique, Stinglhamber, & Swaen, 2014;Dhanesh, 2014;Glavas, 2016;Hur, Moon, & Lee, 2018;Zhou, Luo, & Tang, 2018), few studies have investigated how different kinds of CSR initiative affect employees' CSR perceptions (e.g., M. Farooq, Farooq, & Jasimuddin, 2014;O. Farooq, Payaud, Merunka, & Valette-Florence, 2014;O.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has mainly focused on the role of employees' involvement and commitment (Hur, Moon, & Lee, 2018;Wang, 2018) or on the adoption of voluntary behavior (Lülfs & Hahn, 2014;Testa, Iraldo, & Daddi, 2018). Although these topics are relevant in terms of explaining the CSR commitment of a company, they only analyze the employee-employee or organization-employee relation from a static perspective.…”
mentioning
confidence: 99%
“…The research of El-Kassar et al [66] indicated that employee identification mediates the relationship between CSR and normative commitment. Hur et al [21] explained with social identity theory that CSR perceptions influence employees to cultivate organizational civil norms in order to further enhance their positive identification with their organization, which prevents employees from engaging in CWB.…”
Section: Mediator Of Organizational Identificationmentioning
confidence: 99%
“…Ford and Richardson [17] pointed out that situational factors often exert influences on an individual's ethical or unethical decision behavior. As CSR publicity has been proven to be positively linked with employees' organizational citizenship behavior (OCB) (e.g., [18,19]), and can even act to some extent as a preventive against counterproductive work behavior (CWB) (e.g., [20,21]), we wonder whether the hypocrisy of a corporation may affect employees' CWB. Employees often engage in CWB in an organization [22], and by studying the relationship between corporate hypocrisy and CWB, we can obtain a better understanding of how corporate hypocritical behavior can exert a negative influence on employees' behaviors.…”
Section: Introductionmentioning
confidence: 99%